2016
DOI: 10.4025/jphyseduc.v27i1.2736
|View full text |Cite
|
Sign up to set email alerts
|

Influência do conhecimento tático processual no comportamento tático durante diferentes pequenos jogos no futebol

Abstract: Este estudo comparou o comportamento tático de jogadores de futebol com diferentes níveis de conhecimento tático processual (CTP) durante Pequenos Jogos (PJ) praticados com superioridade numérica. Dezoito atletas de futebol do sexo masculino configuraram seis equipes de três jogadores cada, três delas compostas pelos atletas com maior desempenho no teste de CTP e as outras três equipes constituídas pelos jogadores com menor desempenho. Realizaram-se seis dias de coleta, totalizando 24 séries de jogos de 4 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The results revealed that a greater number of interceptions, dribbles and ball receptions were performed when the number of players was increased permanently, maybe due to increased interactions between attackers and defenders. By contrast, in the game format where a wildcard player played always an attacking role when a team recovered the ball, a higher number of passes and turns were completed, perhaps because "numerically superior settings represent an important for the construction of game models based on an organized attack and on the development of principles related to an offensive construction" [76] (p. 10). Nevertheless, the effect of the number of players on tactics was only analysed in the study by Castelao et al [39] and no significant differences were found.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that a greater number of interceptions, dribbles and ball receptions were performed when the number of players was increased permanently, maybe due to increased interactions between attackers and defenders. By contrast, in the game format where a wildcard player played always an attacking role when a team recovered the ball, a higher number of passes and turns were completed, perhaps because "numerically superior settings represent an important for the construction of game models based on an organized attack and on the development of principles related to an offensive construction" [76] (p. 10). Nevertheless, the effect of the number of players on tactics was only analysed in the study by Castelao et al [39] and no significant differences were found.…”
Section: Discussionmentioning
confidence: 99%
“…The 3vs.3 SSG was chose for investigation because it allows all the decisional possibilities present in the formal game 12 . The SSG were played on a 36x27 meters field area with two goals sized 5x2 meters 7,24 . All experimental sessions occurred at the same time of the day to standardize the effect of the circadian rhythm 25 .…”
Section: Methodsmentioning
confidence: 99%
“…These tactical skills represent players' ability to understand and apply game principles 5 , which support players' decision-making. Therefore, several authors have proposed the assessment of players' knowledge about game principles as an important part of the teaching-learning process [6][7][8] . Previous studies [9][10][11] have used the System of Tactical Assessment in Soccer -FUT-SAT 12 -to analyze players' tactical skills related to Fundamental Tactical Principles, which represent a set of basic rules that guide the action of players and teams in the two phases of the game 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations